PELA SEBAGAI SARANA PENYELESAIAN KONFLIK ANTARA SUKU ALUNE DAN WEMALE DI KABUPATEN SERAM BAGIAN BARAT PROPINSI MALUKU - Makaruku, Steven (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 1 (2013), 2013)
Research about “Pela” as faulity solution conflict berween villages on Tribe Alune and Wemale in district Kairatu, Wets Seram, with aim to giving description all at once input for peoples. Gevernment and sympathy of law in this area about important Constribution Pela on regulatury living people. This research do that on four village whose have design relation its clear, that is : village Tihulale with village Hukuanakota and village Rambatu with Village Abio. The Research Object head of people, Figure Customs, Figure of peoples and people member. The method of research characteristic is descriptive analyse and analyse of data do qualitative. From analyse product have a concluded that “Angkat Pela and Panas Pela” to make resemble two faulity important which until now. This enough to give C onstribution whose to signify for people a finished several conflict which rise. From “Angkat Pela and Panas Pela” the people can find conscious self to always look after, to make care and system of life that fixed, save and peace.
Keywords: Pela; Constribution; Conflict